Interelasi Persepsi Siswa SMK Terhadap Redefinisi Campur Kode Dalam Judul Berita Politik Di Media Massa Berbasis Online Pada Detik.Com Edisi: September 2016 - Royani, Erma; , Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2017)
This study has three objectives. (1) Describe the code mixed analysis in the headline of political news in online-based mass media on detik.com edition: September 2016. (2) Describe the redefinition of the word contained in the title of political news in the online-based mass media detik.com edition: September 2016. (3) Describe the interaction of SMK students' perceptions of the use of online-based mass media on detik.com edition: September 2016. The data in this research is a form of mixed code of news headline and statement form from student questionnaire SMK. This research uses library techniques, gather techniques, record techniques, quistionnaires in data collection. Data analysis technique used is interactive analysis model. There are three things that need to be addressed in this research. (1) There are mixed word codes, mix phrase codes, and mix reduplication code in the headline of political news in an online-based mass media on detik.com edition: September 2016. (2) There are ten words of code mixed redefinition based on dominating data mix The code of the political news headline. (3) There is an interrelation of SMK students' perceptions of code mixing redefinition in the title of political news in online-based mass media on detik.com edition: September 2016. Interrelation is proved by 44 respondents statement stating media intermediaries HP, Laptop, Notbook, Netbook, and computer As access to information quickly and easily obtained for searching online news information. Keywords: code mixing, political news, redefinition.